A Role of the Inflammasome in the Low Storage Capacity of the Abdominal Subcutaneous Adipose Tissue in Obese Adolescents - Kursawe, Romy (Diabetes, 2016)
The innate immune cell sensor leucine-rich–containing family, pyrin domain containing 3 (NLRP3) inflammasome controls the activation of caspase-1, and the release of proinflammatory cytokines interleukin (IL)-1β and IL-18. The NLRP3 inflammasome is implicated in adipose tissue inflammation and the pathogenesis of insulin resistance. Herein, we tested the hypothesis that adipose tissue inflammation and NLRP3 inflammasome are linked to the downregulation of subcutaneous adipose tissue (SAT) adipogenesis/lipogenesis in obese adolescents with altered abdominal fat partitioning. We performed abdominal SAT biopsies on 58 obese adolescents and grouped them by MRI-derived visceral fat to visceral adipose tissue (VAT) plus SAT (VAT/VAT+SAT) ratio (cutoff 0.11). Adolescents with a high VAT/VAT+SAT ratio showed higher SAT macrophage infiltration and higher expression of the NLRP3 inflammasome–related genes (i.e., TLR4, NLRP3, IL1B, and CASP1). The increase in inflammation markers was paralleled by a decrease in genes related to insulin sensitivity (ADIPOQ, GLUT4, PPARG2, and SIRT1) and lipogenesis (SREBP1c, ACC, LPL, and FASN). Furthermore, SAT ceramide concentrations correlated with the expression of CASP1 and IL1B. Infiltration of macrophages and upregulation of the NLRP3 inflammasome together with the associated high ceramide content in the plasma and SAT of obese adolescents with a high VAT/VAT+SAT may contribute to the limited expansion of the subcutaneous abdominal adipose depot and the development of insulin resistance.